Os Jesuítas e a organização da Universidade Católica de Goiás (1954-1979) - Costa, Maximiliano Gonçalves da (2025)
This thesis is linked to the Research Line State, Policies, and History of Education of the Graduate Program in Education at the Faculty of Education of the Federal University of Goiás (PPGE/FE/UFG). Its objective is to understand the role of the Society of Jesus in Catholic higher education in Goiás, both in the foundation of the Catholic University of Goiás (UCG) and in the first twenty years of the institution’s administration. This study is the result of historical research that contributes to investigations in the History of Education and the Catholic Church in Goiás. The research adopted a qualitative approach and, through documentary and bibliographical support, sought to analyze the actions of Jesuit priests in Goiânia, focusing on the establishment and systematization of Catholic higher education between the years 1954 and 1979. The chronological framework covers the period during which the Jesuits were responsible for Catholic higher education in Goiás. This timeframe spans from 1954, when the Jesuits arrived in Goiânia at the request of the then Archbishop of Goiás, Dom Emanuel Gomes de Oliveira, to take over the coordination of the Faculty of Philosophy, Sciences, and Letters—the main precursor to the Catholic University of Goiás—until 1979, when the Jesuits left the administration and academic work at the university amid internal conflicts with the local hierarchy and a group of professors, handing over the institution to the care of the Archdiocese of Goiânia. During this period, the institution had four Jesuit rectors: Fr. Paulo de Tarso Nacca (1959–1962), Fr. Ormindo Viveiros de Castro (1963–1967), Fr. Cristóbal Álvarez Garcia (1968–1973), and Fr. José Carlos de Lima Vaz (1973–1979). Thus, the research focuses on the Jesuits’ actions and the contribution of this religious order to the early development of higher education in Goiás. The study is based on the analysis of documentary sources such as correspondence, meeting minutes, yearbooks, statutes, reports, newsletters, contracts, and newspaper clippings—many of which are unpublished and had not been previously accessed in academic studies. Regarding the writing of the historical narrative, in addition to documentary sources, theoretical references on the history and activities of the Society of Jesus were used, including works by Loyola (1997, 2006), Herraiz (2002), O'Malley (2004), Durkheim (2020), Leite (1938), Miranda (2011), and Magalhães (2015). For the construction of theoretical criticism, the study is supported by the works of Bourdieu (1983, 1987, 1989, 2004). The tension between the Jesuits and the Archdiocese of Goiânia resulted in the end of the Jesuits’ mission at the university in September 1979. The reasons that led to this event are related to financial and patrimonial issues, the influence of Liberation Theology concepts, and a power plan in progress, which resulted in its break with the Catholic University of Goiás.